Ignition of dense, inhomogeneous fuel sprays at elevated pressures and temperatures. (1st August 2022) - Han, Minchao; Gordon, Robert L.; Talei, Mohsen; Lacey, Joshua S.
Abstract: This paper investigates the ignition of inhomogeneous, dense n-heptane sprays, injected with a prototype injector designed for the Engine Combustion Network's Spray G research. The spray is ignited by a traversable laser spark in a combustion Constant Volume Chamber (CVC) at various chamber and fuel pressures and temperatures. High-speed schlieren, diffuse back-illumination (DBI) imaging, and high-speed OH* chemiluminescence are used to visualize the spray injection and flame evolution. The influences of chamber and fuel conditions on probabilities of flame kernel formation and flame generation are analysed at each test condition. Several key parameters such as minimum ignition energy, liquid-based Weber number, Reynolds number and laminar flame speed are used in an attempt to explain the observed behaviour. It is found that the increase of chamber temperature increases the ignition probability, which can be associated with the impact of temperature on the evaporation rate. The impact of chamber pressure on ignition probability can also be explained by considering the variations of liquid-based Weber number and Reynolds number for these cases. As the chamber pressure increases, these non-dimensional parameters decrease, indicating a larger droplet size for a higher pressure and therefore reduced ignition probability. However, the variations of liquid-based Weber number and Reynolds number cannot explain the effects of fuel pressure on ignition probability. In fact, the opposite behaviour to that expected from the changes of these parameters, i.e. reduction in ignition probably for higher fuel pressure is observed. Also, the laminar flame speed can only explain the impact of temperature on flame propagation after ignition. Overall, the presented results show a complex picture for kernel formation and propagation for the cases studied in this paper. While established theoretical arguments can explain the effects of temperature on ignition probability, a deeper understanding of the inter-relationships of the effects of pressure is needed. Highlights: World-first experiments on dense, inhomogeneous spray ignition at elevated conditions. Simple theoretical arguments can explain the effects of chamber temperature. The laminar flame speed can only explain the impact of temperature changes. The effects of pressure need further understanding of the physical phenomena involved.